Morbidity Pattern and Health Education for School age Children in Karachi (Medical Forum Monthly, 2024)
Objective: To screen morbidities among school age children, to assess health education need to prevent these diseases and to compare morbidities with national and international patternsStudy Design: Cross Sectional Epidemiological StudyPlace and Duration of Study: This study was conducted at DIMC, DUHS, Karachi during February and March 2012.Materials and Methods: This study was conducted of school children of Karachi. Sample size; 125 children from 6 primary, kg and nursery classes data was collected on pre -designed and pre- tested proformaResults: Total 22 morbidities were identified on clinical examination and anthropometry methods common morbidities were max in ear, scabies, lice infestation, alopecia, anemia, and underweight, DNS, Rhinorrhea, 21.5 % children had no morbidity while 28.8 % needed primary health care/ first aid or simple treatment or referral while 71% needed health education, hygiene or nutrition supplements. Morbidities are same as reported from Pakistan and Indian studies published Journals and books and all morbidities were preventableConclusion: School age children are suffering from common preventable diseases they need primary health care education hygiene and nutrition supplement to improve their health Medical Universities NGOs and Education and Health Department can manage by health camps or by formal school health services programme.